Faktor-Faktor Yang Mempengaruhi Nilai Informasi Laporan Keuangan Pemerintah Derah Kota Pekanbaru - Parlindo, Parlindo (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2022)
Objective. This study aims to analyze the factors that influence the value of information on the financial statements of the Pekanbaru City Government. at the Pekanbaru City Regional Apparatus Organization. This study uses quantitative methods using primary data obtained from questionnaires. The population of this study is the head of the finance department, staff of the finance sub-section, and PPK (Financial Administration Officer). Research Method. The sample in this study was 117 respondents. The data were processed using multiple linear regression analysis with the help of SPSS Version 25. The results showed that the partial test of the Regional Financial Supervision variables. Conclusion. Contains a brief summary of the conclusions that answer the objectives of this study and includes suggestions that can be used for further development.